Uniportal VATS Coil-Assisted Resections for GGOs. (12th May 2019) - Congedo, Maria Teresa; Iezzi, Roberto; Nachira, Dania; Larici, Anna Rita; Chiappetta, Marco; Calandriello, Lucio; Vita, Maria Letizia; Meacci, Elisa; Porziella, Venanzio; Ismail, Mahmoud; Manfredi, Riccardo; Margaritora, Stefano
Abstract : Backgrounds . Although uniportal video-assisted thoracic surgery (VATS) theoretically allows the direct palpation of any zone of the lung through a small incision, sometimes it can be difficult to localize pure ground-glass opacities anyway. The aim of this study is to evaluate the usefulness and safety of preoperative computed tomography (CT)-guided microcoil localization of GGO nodules in patients undergoing uniportal VATS lung resection. Methods . The clinical data and CT images of 30 consecutive patients (30 pulmonary nodules) who underwent preoperative CT-guided coil localization and subsequent uniportal VATS resection, from January 2017 to October 2018, were reviewed. Results . All the CT-localization procedures have been performed with success (30/30) and the mean procedure time was 35±15 minutes. The mean size of the nodules was 15, 53±6, 72 mm, and the mean distance of the nodules from the pleural surface was 19, 08±12, 08 mm. Eleven nodules (36, 7%) were pure ground-glass opacities and 19 (63, 3%) were mixed ground-glass with a solid component of 50% or more. In 5 cases, the localization procedure was complicated by asymptomatic pneumothoraxes and in 1 case the pneumothorax required chest tube insertion. In any case a conversion to thoracotomy was avoided because all nodules were identified and resected through uniportal VATS. Conclusions . Preoperative CT-guided coil localization seems to be a feasible, safe, and accurate procedure. It makes uniportal VATS an easy approach even for resecting small, deep, and impalpable nodules.